1990
DOI: 10.2307/30145474
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis: B Perceptions, Knowledge and Vaccine Acceptance Among Registered Nurses in High-Risk Occupations in a University Hospital

Abstract: We employed a questionnaire to survey 334 registered nurses regarding their knowledge, perceptions and vaccine acceptance for Hepatitis B virus (HBV) infections. The study population was those persons working in areas considered at high-risk for contracting HBV. The nurses were asked to provide information regarding blood and body fluid exposures and the reporting of these exposures. The questionnaire was completed by 169 nurses (50.6%). Less than half of the respondents (42%) had been vaccinated. We found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 6 publications
(2 reference statements)
1
9
0
Order By: Relevance
“…Future research could investigate this motivation link to this type of health behavior. Adult vaccinations have been examined by other researchers and findings have shown that additional effort must be made to get high compliance with vaccination recommendations for adults, including patient education and automated vaccination tracking systems (Tung et al, 2003), nurse case management (Nyamathi et al, 2015), and having the vaccinations available in convenient locations and at convenient times (Spence & Dash, 1990). Among high-risk groups such as injection drug users, providing incentives for receiving the vaccination, providing assistance with transportation to a health care provider, or having the vaccinations onsite at methadone treatment programs were all associated with greater vaccination dose compliance (Des Jarlais et al, 2001;Trubatch et al, 2000).…”
Section: Personal Control Beliefsmentioning
confidence: 99%
“…Future research could investigate this motivation link to this type of health behavior. Adult vaccinations have been examined by other researchers and findings have shown that additional effort must be made to get high compliance with vaccination recommendations for adults, including patient education and automated vaccination tracking systems (Tung et al, 2003), nurse case management (Nyamathi et al, 2015), and having the vaccinations available in convenient locations and at convenient times (Spence & Dash, 1990). Among high-risk groups such as injection drug users, providing incentives for receiving the vaccination, providing assistance with transportation to a health care provider, or having the vaccinations onsite at methadone treatment programs were all associated with greater vaccination dose compliance (Des Jarlais et al, 2001;Trubatch et al, 2000).…”
Section: Personal Control Beliefsmentioning
confidence: 99%
“…When examining hepatitis B immunization among HCWs in the early 1990s, Mundt (1992) determined that reported acceptance rates for vaccination ranged from 27 to 58% and probably averaged around 50%. In an early study of RNs employed at a large university hospital, Spence and Dash (1990) found that only 41% had received the vaccine.…”
Section: Rates Of Vaccination Against Hepatitis Bmentioning
confidence: 99%
“…Among the attitudinal factors, three common reasons were found to explain the failure to he vaccinated. The first involved fear of the side-effects, concern about the efficacy of vaccination, and other fears including general fear, fear of AIDS and fear of contracting jaundice/ Hepatitis B (Briggs & Thomas 1994, Murata & Young 1993, Israsena et al 1992, Mckenzie 1992, Alexander et al 1990, Spence & Dash 1990, Scapa et al 1989, Harward et al 1988, Heyworth 1988, Bodenheimer et aL 1986, Kwon et aL 1984, Triger 1984. The second reason was related to organizational self-motivation factors such as being too busy, inertia and inability to schedule an appointment (Briggs & Thomas 1994, Murata & Young 1993, Mckenzie 1992, Astbury & Baxter 1990, Spence & Dash 1990, Kwon et al 1984.…”
Section: Literature Reviewmentioning
confidence: 99%